The Effect of Cash Turnover and Quick Ratio on Profitability: Study Of Multinational Companies Producing Chemicals (2019-2021 Period) - Surachman, Syania Rosy; Ningsih, Tri (P3M, STIE Pasundan, Bandung, Indonesia., 2023)
The enduring viability of a corporation is intrinsically linked to its primary objective of optimizing financial gains. Attaining this goal is crucial for guaranteeing the company's durability and ongoing prosperity. Within this environment, it is crucial to comprehend the complex interconnection among financial data. This study mainly aims to examine the impact of Cash Turnover and Quick Ratio on Profitability of Multinational Companies Producing Chemicals . from 2019 to 2021.The company's enduring prosperity hinges on efficient financial management, with the primary objective being earnings maximization. To explore this phenomenon in depth, a research method that combines associations and quantitative data is utilized. The data utilized in this investigation are derived from the official website of Multinational Companies Producing Chemicals. and pertains to the period from 2019 to 2021.The research findings provide a detailed comprehension of the interaction between financial variables and Profitability for Multinational Companies Producing Chemicals. Firstly, the study emphasizes Cash Turnover's favorable and substantial impact on Profitability, specifically Return on Assets (ROA). The impact is measured as 46.4%, highlighting the significant contribution that efficient cash turnover makes to improving the company's Profitability. This condition highlights the significance of efficiently managing cash flows to maximize financial performance.Moreover, the study reveals that the Quick Ratio has a substantial and beneficial effect on Profitability (ROA) with a magnitude of 19.3%. The Quick Ratio, a metric that assesses a company's capacity to meet its short-term obligations using its most readily available assets, is significant in determining Profitability. This observation implies that upholding a favorable proportion of liquid assets to immediate liabilities benefits the company's overall Profitability.Moreover, the study examines the collective influence of Cash Turnover and Quick Ratio on Profitability (ROA). The combined impact of these characteristics was determined to be both favorable and statistically significant, totaling 65.8%. This condition highlights the need to consider many financial indicators together to achieve improved Profitability.